"MUSIQUE DU BURUNDI” - OCR 40, 33 r.p.m. Disques OCORA, Maison de l'Office de Radio-diffusion Television Francaise, 116 Av. de President Kennedy, Paris. - Tracey, Andrew (International Library of African Music, 1970)
Some first-class music recorded in Burundi in April/May, 1967, by Michel Vuylsteke, and reproduced with first-class quality.
Keywords: Central Africa; African Music; Burundi